I am still not a loser - Loser, Barry; Smith, James, 1975- (London : Jelly Pie, 2013)
Barry Loser has a problem and that his is best friend has been stolen by Gordon Smugly.
School Library Journal
School Library Journal, December 2013
3-6
English.
Keywords: Boys -- Juvenile fiction; Boys -- Fiction; Humorous stories; Boys -- Fiction; Humorous fiction; Humorous fiction